96 Mixed Adenoneuroendocrine Carcinoma in Crohn's Disease: A Case Report and Literature Review. (4th May 2021) - Cuthbert, M; Cuthbert, R; Karamsadkar, S; Minicozzi, A; Chan, C
Abstract: Introduction: Mixed adenoneuroendocrine carcinoma (MANEC) is a rare neoplasm with dual adenocarcinomatous and neuroendocrine differentiation. Subgroup analysis demonstrates an increased frequency of both adenocarcinomas and neuroendocrine tumours in patients with Crohn's disease (CD), though the incidence of MANEC is unknown. Method: A 58-year-old male with a 31-year history of CD presented with small bowel obstruction. After failed conservative management, the patient underwent right hemicolectomy, with subsequent histology demonstrating MANEC. A literature search was performed to identify further cases of patients with concomitant MANEC and CD. Results: 11 cases were identified. The mean duration of CD before presentation was 19.5 years, and 58% of cases involved the terminal ileum. 60% of cases demonstrated nodal spread and metastatic disease was evident in 25%. 42% of patients with MANEC were initially treated for an exacerbation of CD. Conclusions: MANEC is a rare tumour of uncertain aetiology. The terminal ileum is commonly affected, with most cases exhibiting a longstanding CD history. Diagnosis is challenging, with symptoms of MANEC mirroring exacerbations of CD. Future research should strive to identify imaging modalities or biochemical markers which aid in distinguishing the two pathologies, preventing futile medical management of MANEC, and reducing the risk of metastatic spread due to delayed diagnosis.